From sound to symbol: orthographic semantization in Maya hieroglyphic writing. Issue 2 (3rd July 2017) - Matsumoto, Mallory E.
ABSTRACT: Scholars have been aware for some time of the linguistic and orthographic processes through which phonograms, signs that communicate an established phonetic value but have no inherent semantic content, may be derived from logographs, which encode semantic meaning, but whose phonetic value can vary depending on the linguistic context. However, they have largely ignored the possibility of the reverse, of phonograms transforming into logographs. This phenomenon, referred to here as orthographic semantization, entails the reinterpretation of a known sequence of one or more phonetic signs as conveying an inherent semantic value. At the same time, the original phonetic reading of the reinterpreted sign or sign sequence becomes obscured or changes completely, even if the graphic form remains the same. This paper explores evidence of this process in Maya hieroglyphic writing by examining cases of overspelling and incongruent or redundant phonetic complementation. Significantly, the underlying motivations for orthographic semantization differ by context. Hence, studies of this phenomenon can yield insight into the sociocultural aspects of script development and use, including language contact, script ideology, script transfer, or interruptions in scribal practice. Such research promises to enhance our understanding of the dynamic relationship between writing, its users, and spoken language.